Avaliação de custos das internações de gestantes hipertensas em Hospital Universitário do interior paulista - Lima, Silvana Andréa Molina [UNESP]; Cavassini, Ana Cláudia Molina; Manso, Ligia Nogueira; Peraçoli, Jose Carlos [UNESP]; Costa, Roberto Antonio de Araújo [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (My University, 2012)
This study aimed at identifying the hospitalization costs for delivery of hypertensive pregnant women at Maternity of University Hospital in inner São Paulo state. It is a quantitative, descriptive and exploratory study. For data collection, the direct and indirect costs were identifi ed in order to determine the hospitalization costs of patients diagnosed with arterial hypertension during pregnancy and delivery. After analyzing the results, it was observed that the hospitalization period was of one day during pregnancy and fi ve days for delivery; cesarean section was performed in 64.9% of hypertensive pregnant women; the mean total cost was of R$ 348,87 (US$ 187.56)/ hospitalization during pregnancy, R$ 2.656,60 (US$ 1,428.27)/hospitalization for the cesarean section and R$ 2.316.09 (US$ 1,245.20)/ hospitalization for vaginal delivery. It can be concluded that the analysis of hypertensive patients’ hospitalizations cost is important, since these are hospitalizations that require a special care, leading to increased service costs.

Este estudo objetivou identifi car os custos das internações de gestantes portadoras de Hipertensão Arterial na Maternidade de Hospital Universitário do interior de São Paulo. Trata-se de um estudo quantitativo, descritivo e exploratório. Para coleta de dados, foram identifi cados os custos diretos e indiretos para determinação dos custos das internações de pacientes com diagnóstico de Hipertensão Arterial durante a gestação e parto. Após análise dos resultados, verifi cou-se que o tempo de internação foi de um dia durante a gestação e cinco dias para o parto; a incidência de cesárea foi de 64,9% entre as hipertensas; o custo médio total foi de R$ 348,87/ internação durante a gestação, R$ 2.656,60/internação para o parto cesárea e R$ 2.316,09/internação para o parto vaginal. Conclui-se que é importante a realização de análise dos custos das internações de pacientes hipertensas, pois são internações que necessitam de cuidados especiais e podem elevar os custos do serviço.
Assessment of hypertensive pregnant women’s hospitalization costs at a University Hospital in São Paulo state
Keywords: Costs and cost analysis; Hospital costs; Hypertension, pregnancy-induced; Health management; Custos e análise de custo; Custos hospitalares; Hipertensão induzida pela gravidez; Gestão em saúde